2016
DOI: 10.1016/j.neurobiolaging.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem MRI: a novel window into the neurobiology of late life cognitive decline

Abstract: This study tested the hypothesis that indices of brain tissue integrity derived from postmortem MRI are associated with late life decline in cognitive function and dementia, over and above contributions from common age-related neuropathologies. Cerebral hemispheres were obtained from 425 deceased older adults who had undergone two or more annual cognitive assessments, which included clinical diagnosis of dementia. Specimens underwent MRI to produce maps of transverse relaxation rate, R2. Voxelwise regression r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…This current study extends our previous work (Dawe, et al, 2014, Dawe, et al, 2016) in three important ways. First, we focus on a complementary clinical outcome, i.e.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This current study extends our previous work (Dawe, et al, 2014, Dawe, et al, 2016) in three important ways. First, we focus on a complementary clinical outcome, i.e.…”
Section: Introductionsupporting
confidence: 88%
“…Using data from ex vivo imaging, we previously showed that prolonged transverse relaxation time is correlated with pathologic burdens of AD, infarcts and hippocampal sclerosis, thus providing direct evidence for the neuropathologies’ involvement in these alterations (Dawe, et al, 2014). Further, we demonstrated that common neuropathologic indices are not solely responsible for the relationship between transverse relaxation alterations and late life cognitive performance (Dawe, et al, 2014, Dawe, et al, 2016). …”
Section: Introductionmentioning
confidence: 84%
“…Therefore, we focused on a composite R 2 measure that captures the overall relaxation associated with cognitive decline above and beyond the influence of commonly measured neuropathologic conditions. 11 …”
Section: Methodsmentioning
confidence: 99%
“…Ex-vivo MRI scans show high correlation with antemortem imaging (Dawe et al 2016) and were conducted on a 3 Tesla MRI scanner using a 2D fast spin-echo sequence with multiple echo-times (TEs), producing estimates of relaxation rates (R 2 ) for each voxel. R 2 values are the inverse of T 2 values.…”
Section: Neuroimaging Data Processingmentioning
confidence: 99%
“…We followed an imaging omics approach to discover relationships between omics and neuroimaging, using~200 brains with paired omics and ex-vivo neuroimaging Dawe et al 2009;Dawe et al 2016;Kotrotsou et al 2014;Kotrotsou et al 2015), from two longitudinal cohort studies of aging Bennett et al 2005). Our approach to finding relationships between brain omics and structure is analogous to typical neuroimaging studies and imaging genetics studies (Fig.…”
Section: Introductionmentioning
confidence: 99%